Alfalfa Flavonoids Mitigate Salmonella‐Induced Colitis via the Keap1‐Nrf2 and TLR4/NF‐κB/COX‐2 Pathways - Xiaoli Qin; Yan Lu; Yawen Luo; Yafang Cui; Kai Zhao; Yang He; Muhammad Aziz ur Rahman; Shengnan Min; Wenfang Wang; Fuyu Yang; Binghai Cao; Huawei Su (Food Frontiers)
ABSTRACT Alfalfa is rich in flavonoid compounds, which are known for their antioxidative and anti‐inflammatory properties, suggesting therapeutic potential for alfalfa flavonoids (AF) in inflammation‐related diseases. This study investigated the effects of AF on Salmonella‐induced colitis, a severe inflammatory bowel disorder characterized by oxidative damage and inflammatory response. In vitro, antioxidant assays revealed AF's concentration‐dependent radical scavenging, significantly reducing electron paramagnetic resonance (EPR) signals for HO• and O2•− by 42% and 54%, respectively. In vivo, AF treatment significantly mitigated body weight (BW) loss by 6%, increased colon length by 11%, and reduced liver and spleen weights by 19% and 81%, respectively, compared to the colitis group. Mechanistically, AF suppressed inflammation by downregulating the Toll‐like receptor 4 (TLR4)/IκB/nuclear factor‐κB (NF‐κB)/cyclooxygenase‐2 (COX‐2) pathway and inhibiting nucleotide‐binding domain‐like receptor protein 3 (NLRP3) inflammasome activation, thereby lowering levels of pro‐inflammatory cytokines (tumor necrosis factor alpha [TNF‐α], interleukin 6 [IL‐6], interleukin 1 beta [IL‐1β]). Concurrently, AF enhanced antioxidant defense via the Kelch‐like ECH‐associated protein 1 (Keap1)‐nuclear factor erythroid 2‐related factor 2 (Nrf2) pathway, reducing reactive oxygen species (ROS) and malondialdehyde (MDA) levels while increasing catalase (CAT) (69%), glutathione peroxidase (GPx) (83%), and superoxide dismutase (SOD) (21%) activities. Moreover, AF preserved epithelial and mucosal barriers by reducing apoptosis and upregulating tight junction proteins (Claudin1, ZO‐1, E‐cadherin) and goblet cell marker Ulex europaeus (Gorse) Agglutinin I (UEA‐1). Microbiota analysis revealed that AF significantly enriched beneficial bacteria, including Akkermansia, Oscillibacter, and butyrate‐producing taxa, thereby counteracting Salmonella‐induced dysbiosis. Furthermore, AF restored the disrupted profile of short‐chain fatty acids (SCFAs), strengthening the relationship between symbiotic microbiota and mucosal defense. Overall, AF exerted multifaced protection against Salmonella‐induced colitis by alleviating oxidative stress, stabilizing intestinal homeostasis, and thus attenuating inflammation. These findings make AF a promising phytopharmaceutical for the prevention and treatment of inflammatory diseases.